The influence and effectiveness of film tourism in travel decision making / Shahirah Ab Razak and Umira Odzlan - Ab Razak, Shahirah; Odzlan, Umira (Faculty of Hotel and Tourism Management, 2013)
The research is aim to study on the influence and the effectiveness of film tourism in travel decision making. The objective of the study is to access the effectiveness of film-tourism and to indicate whether film-tourism can influence people to travel to the viewed destinations. The populations are among tourists who visit Melaka state where the researcher mainly focuses in two areas which are Bandar Hilir and Ayer Keroh. The researcher used questionnaire data collection method to study the film tourism influences in travelling activities. A total number of 165 questionnaires were distributed to the tourist who visits Melaka. The questionnaires were collected right after the respondents completed the survey forms. The survey is undertaken throughout May 2013. The results revealed that and research objective where the effectiveness of the film tourism has being justified where most of the respondents were agreed that film tourism influence their overall travel decision making. Therefore this new phenomenon could create more excitement in promoting product and services offered yet effective and efficient.